Financial student aid and enrollment into higher education: new evidence from Germany - Viktor Steiner; Katharina Wrohlich (Deutsches Institut für Wirtschaftsforschung (DIW), 2008)
We estimate the elasticity of enrollment into higher education with respect to the amount of means tested student aid (BAfoeG) provided by the federal government using the German Socioeconomic Panel (SOEP). Potential student aid is derived on the basis of a detailed taxbenefit microsimulation model. Since potential student aid is a highly non-linear and discontinuous function of parental income, the effect of BAfoeG on students' enrollment decisions can be identified separately from parental income and other family background variables. We find a small but significant positive elasticity similar in size to those reported in previous studies for the United States and other countries.
Keywords: H52; H24; I28; 330; Higher Education; Financial Incentives; Competing Risk Model; Studienfinanzierung; Studium; Bildungsverhalten; Ökonomischer Anreiz; Deutschland